Human Cytomegalovirus Immediate-Early mRNA Detection by Nucleic Acid Sequence-Based Amplification as a New Parameter for Preemptive Therapy in Bone Marrow Transplant Recipients - Gerna, Giuseppe (American Society for Microbiology, 2000)
Human cytomegalovirus (HCMV) infection was monitored retrospectively by qualitative determination of immediate-early (IE) mRNA by nucleic acid sequence-based amplification (NASBA) in a series of 51 bone marrow transplant (BMT) recipients. The qualitative results for IE mRNA obtained by NASBA were compared with those obtained by prospective quantitation of HCMV viremia and antigenemia and retrospective quantitation of DNA in blood (DNAemia) by PCR as well as by qualitative determination of late pp67 mRNA by NASBA. On the whole, of the 39 HCMV-positive patients (all asymptomatic), HCMV was detected in 14 (35.9%) by quantitation of viremia, 15 (38.5%) by detection of pp67 mRNA by NASBA, 32 (82.1%) by quantitation of DNAemia, and 33 (84.6%) by quantitation of antigenemia, while HCMV was detected in 38 (97.4%) patients by detection of IE mRNA by NASBA. In the immunocompetent host, IE mRNA was not detected by NASBA in 100 blood donors or during reactivated infections in 30 breast-feeding mothers. Likewise, NASBA did not detect IE mRNA in 56 solid-organ transplant recipients in the first 21 days after transplantation. By using NASBA for detection of IE mRNA as the reference standard for detection of HCMV infection in blood samples, the diagnostic sensitivities were 67.7% for quantitation of DNAemia, 59.0% for quantitation of antigenemia, 18.3% for detection of pp67 mRNA by NASBA, and 16.0% for quantitation of viremia. Specificities and negative and positive predictive values were >90.0, >70.0, and >80.0%, respectively, for all four assays. The mean times to first HCMV detection after bone marrow transplantation were 37.7 ± 15.4 days for detection of IE mRNA by NASBA, 39.6 ± 15.6 days for quantitation of antigenemia, 40.9 ± 15.2 days for quantitation of DNAemia, and 43.7 ± 16.3 or 43.7 ± 17.5 days for quantitation of viremia and detection of pp67 mRNA by NASBA, respectively. On the whole, 31 BMT recipients received preemptive therapy by using confirmed antigenemia positivity as a cutoff, while 35 patients could have been treated by using NASBA positivity as a cutoff and 31 could have been treated by using quantitation of DNAemia as a cutoff. In single patients, IE mRNA was detected in every episode of active HCMV infection, mostly preceding and sometimes accompanying antigenemia and DNAemia, whereas pp67 mRNA was detected only concomitantly with the highest peaks of infection. HCMV IE mRNA detection may represent a useful parameter for initiation of preemptive therapy in BMT recipients.